2019
DOI: 10.3390/rs11131628
|View full text |Cite
|
Sign up to set email alerts
|

Copula-Based Abrupt Variations Detection in the Relationship of Seasonal Vegetation-Climate in the Jing River Basin, China

Abstract: Understanding the changing relationships between vegetation coverage and precipitation/temperature (P/T) and then exploring their potential drivers are highly necessary for ecosystem management under the backdrop of a changing environment. The Jing River Basin (JRB), a typical eco-environmentally vulnerable region of the Loess Plateau, was chosen to identify abrupt variations of the relationships between seasonal Normalized Difference Vegetation Index (NDVI) and P/T through a copula-based method. By considerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…Recently, large parts of the greening trend are attributed to ecological conservation projects like the Grain for Green program (Brandt et al 2018, Zhao et al 2019b) aiming at recovering ecosystems, alleviate poverty , Wang et al 2019b and improving ecosystem services (Qiu et al 2020, Liu et al 2008. Methods looking into land use change (Liao et al 2018, rocky desertification control (Jiang et al 2014) and vegetation improvement (Qi et al 2013) were used to indicate the effectiveness of ecological engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, large parts of the greening trend are attributed to ecological conservation projects like the Grain for Green program (Brandt et al 2018, Zhao et al 2019b) aiming at recovering ecosystems, alleviate poverty , Wang et al 2019b and improving ecosystem services (Qiu et al 2020, Liu et al 2008. Methods looking into land use change (Liao et al 2018, rocky desertification control (Jiang et al 2014) and vegetation improvement (Qi et al 2013) were used to indicate the effectiveness of ecological engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Sunspot activity affects the solar radiation received by the earth, thus changing atmospheric pressure and temperature gradients, and affecting weather patterns (Soon et al 2015), so that the ability of plants to obtain water changes, resulting in GPP increases. Some studies have confirmed the complex relationship between atmospheric teleconnection and vegetation variations through changing regional temperatures, evapotranspiration, and soil moisture (Anyamba and Eastman 1996;Gong and Shi 2003;Zhao et al 2019). Changing local climate may lead to biological consequences, including prolonging the growing season, promoting vegetation activities and increasing vegetation growth and carbon uptake.…”
Section: Water Conditions and Atmospheric Circulation Jointly Enhance The Performance Of Ecological Engineeringmentioning
confidence: 98%
“…Vegetation is an important component of earth ecosystems. Numerous studies have been conducted to study the relationship between vegetation and climate change [ 5 , 30 ]. However, there are many studies on the single relationship between vegetation and geology [ 31 , 32 ] or between vegetation and geomorphology [ 4 , 33 ], but few studies [ 1 , 3 ] on the relationship between vegetation and geology–geomorphology comprehensive system.…”
Section: Introductionmentioning
confidence: 99%